2018 Vegetable Production Handbook Chapter 9: Leafy Vegetable Production - Monica Ozores-Hampton; Ramdas Kanissery; Richard N. Raid; Johan Desaeger; Joseph W. Noling; Julian Beuzelin; Christian F. Miller (EDIS, 2018)
This 29-page fact sheet is chapter 9 of the 2018 Vegetable Production Handbook. Written by Monica Ozores-Hampton, Ramdas Kanissery, Richard N. Raid, Johan Desaeger, Joseph, W. Noling, Julien Beuzelin, and Christian F. Miller, and published by the Horticultural Sciences Department, 2018.